Heartstopper. Volume 3 - Oseman, Alice (Oseman, Alice. Heartstopper., 2021)
Now that Charlie and Nick are officially dating, they have to figure out a way to come out to their friends and classmates. When the couple goes on a school trip to Paris, they become more comfortable with their relationship and slowly find the right way to tell their classmates the truth.